TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP JUAL BELI BUKU BAJAKAN DI TOKO BUKU KAIRO KOTA BANDUNG - Wisyahban, Risman; Nuraeni, Neni (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2018)
This research was motivated by the widespread buying and selling of pirated books that occurred in Bandung, one of them in the Cairo bookstore. Book piracy is one form of copyright crime that is prohibited and regulated in the MUI No.1 Year 2003 Fatwa concerning Copyright and Law No.28 of 2014 concerning copyright infringement. This research starts from the idea that the implementation of the sale and purchase of pirated books is a prohibited sale and purchase transaction based on the MUI No.1 Year 2003 Fatwa concerning Copyright and Law No.28 of 2014 concerning Copyright. However, in the implementation of the implementation of the law in the field must also pay attention to aspects of benefits and welfare for both the perpetrators and the impact on the wider community. This research method uses a case study method by conducting in-depth interviews (in-depth interviews), to bookstore owners Cairo City of Bandung. The analysis of the data is by linking the implementation of the sale and purchase of pirated books with the provisions of the law and legislation that apply, namely the Fatwa of MUI No.1 of 2003 concerning Copyright and Law No.28 of 2014 concerning Copyright. The results of this thesis reveal that: (1) that based on the data obtained there has been a sale and purchase of pirated books at the Cairo bookstore in Bandung City. the implementation of bookstore owners accept books from distributors and then sell them to students and the public. (2) while the benefits of buying and selling pirated books (a) never sell out (b) the price of the book is cheaper. Whereas the madharat (a) is very risky to be caught in a criminal case (b) the profits generated are not lawful. (3) according to Sharia Economic Law the sale and purchase of pirated books and the Fatwa of MUI No.1 Year 2003 concerning Copyright or Law No.28 of 2014 pirated sale and purchase constitutes injustice whose laws are unlawful. Harmonization that can be done is that book sellers try to contact authors and publishers so that there is a cheaper edition of the book so that it is affordable for students and the public, or give permission to reproduce with certain agreements.